EKSPERIMENTASI MODEL PEMBELAJARAN THINK PAIR AND SHARE (TPS) DIMODIFIKASI CONTEXTUAL TEACHING AND LEARNING (CTL), THINK PAIR AND SHARE (TPS) DAN KONVENSIONAL PADA BAB BANGUN RUANG SISI DATAR DITINJAU DARI GAYA BELAJAR PESERTA DIDIK - Toipur, Toipur; Mardiyana, Mardiyana; Roswitha, Mania (Jurnal Pembelajaran Matematika, 2013)
Abstract: The objectives of this research were to investigate: (1) which learning model of the TPS modified with CTL, the TPS, and the conventional learning; (2) which students of those with the visual, auditory, and kinesthetic learning styles have a better learning achievement in Mathematics; (3) in each learning style, which learning model of the TPS modified with CTL, the TPS, and the conventional learning results in a better learning achievement in Mathematics; and (4) in each learning model, which learning style of the visual, auditory, and kinesthetic learning styles results in a better learning achievement in Mathematics. This research used the quasi experimental research method with the factorial design of 3 x 3. The population of the research was the students of Islamic Junior Secondary Schools in Tulungagung regency. The samples of the research were taken by using the stratified cluster random sampling technique. The samples of the research consisten of 294 students; 95 students belonged to experiment class one, 93 students belonged to experiment class two, and 106 students belonged to control class. The data of the research were gathered through multiple choice test of learning achievement and questionnaire of learning style. The data of the research were analyzed by using the unbalanced two-way analysis of variance. The results of the research are as follows. 1) The students instructed with TPS modified with CTL have the same learning achievement in Mathematics as those instructed with the TPS. Both the TPS modified with CTL and TPS have a better learning achievement than those instructed with the conventional learning. 2) The students with the visual, auditory, and kinesthetic learning styles have an equal learning achievement in Mathematics. 3) In each learning style, the students instructed with TPS modified with CTL have the same learning achievement in Mathematics as those instructed with the TPS. Both the TPS modified with CTL and TPS have a better learning achievement than those instructed with the conventional learning. 4) In each category of the learning models, the students with the visual, auditory, and kinesthetic learning styles have an equal learning achievement in Mathematics.Keywords: Learning style, think pair and share, contextual teaching and learning.